Los recursos didácticos en el desarrollo de la Lecto-escritura bloque 3, “Lectura” del tercer grado paralelo “B” de la escuela “Zoila Alvarado de Jaramillo”, Loja, 2021-2022. - Vega Quevedo, Sandra Rosalía (2022)
The present investigation titled: The didactic resources in the development of literacy block 3, "Reading" of the third grade parallel "B" of the "Zoila Alvarado de Jaramillo" school, Loja, 2021-2022; Its general objective is: To determine the incidence of didactic resources in the development of reading and writing. The importance lies in strengthening reading and writing through the use of didactic resources taking as a reference the results of the application of the Magellan's Literacy test. This study was carried out under a mixed qualitative-quantitative approach; quasi-experimental design. The methods: scientific, statistical, analytical, synthetic and descriptive were used. The techniques: observation sheet, interview with the teacher, post-test and pre-test of evaluation of Magellan's Literacy. The population consisted of 27 students and 1 teacher. In order to support the improvement of reading and writing in third grade students, the proposal called; "Learning together with the didactic resources to advance in the achievement of Reading and writing" was executed, at the end of which, it is ensured that the students significantly improve their cognitive development in their active participation in the classroom by making use of the prepared didactic resources so that they can interact and play in an environment of motivation and interest for the Reading acquisition level valuing their calligraphic skills. Keywords: Didactic resources, Literacy, teaching methods